Recent progress on sugarcane-bagasse based lactic acid production: technical advancements, potential and limitations - Agrawal, Deepti; Kumar, Vinod (Elsevier, 2023)
India is the largest producer of sugarcane in Asia and its sugar industry represents the second largest agro-based industry. Sugarcane bagasse (SCB), a major waste from sugar industries, is indisputably lignocellulosic biomass (LCB) embedding ∼60 % carbohydrates, making it a renewable source of fermentable sugars. Despite its unique chemical composition, SCB is primarily used for co-generation. The enormous potential of SCB can be unleashed, if sugar platform is created using biochemical route. Sugars serve as feedstock for fermentative production of several renewable fuels and chemicals, considered as key drivers for rapid industrialization. US Department of Energy has projected lactic acid (LA) as one of the top biomass-derived platform chemicals owing to its diverse applications and multi-billion-dollar market. Currently, the industrial production of LA is predominated by microbial fermentation (∼90 %) which principally uses the starchy or sugar-rich edible feedstocks. If its low-cost manufacturing relying on LCB is enabled, it can be a boon for emerging economies like India, strategically strengthening their socio-economic status. The present review showcases the technical advances made in exploiting the biochemical route towards commercial realization of LA production with SCB as the feedstock. It comprehensively discusses strategies developed in the area of pretreatment, saccharification and fermentation, bridging the gap between lab-scale and industrial LA production. It gives a glimpse on downstream processing of SCB-derived LA, which is still in its nascent stage and briefly talks about our perspective on LA as preferred choice for scale-up in “sugar industry” over other bio-based fuels and chemicals.
Keywords: Sugarcane bagasse; Lactic acid; High-solids pretreatment; High-solids saccharification; Downstream processing